Workers' Societal Costs After Knee and Shoulder Injuries and Diagnosis with In-Office Arthroscopy or Delayed MRI: A Cost-Minimization Analysis. Issue 2 (April 2021) - Liu, Joseph; Farr, Jack; Ramos, Omar; Voigt, Jeff; Amin, Nirav
Abstract : Background: The goal of this study was to evaluate the societal costs of using in-office diagnostic arthroscopy (IDA) compared with magnetic resonance imaging (MRI) for the diagnosis of intra-articular knee and shoulder pathology in employed patients receiving Workers' Compensation or disability coverage. The prevalence is estimated at 260, 000 total cases per year. Methods: A cost-minimization analysis of IDA compared with MRI was conducted. Direct costs (in 2018 U.S. dollars) were calculated from private reimbursement amounts and Medicare. Indirect costs were estimated from a societal perspective including effects of delayed surgical procedures on the ability to work, lost income, Workers' Compensation or disability coverage, and absenteeism. Four regions were selected: Boston, Massachusetts; Detroit, Michigan; Denver, Colorado; and San Bernadino, California. Sensitivity analyses were performed using TreeAge Pro 2019 software. The base assumption was that it would take approximately 4 weeks for a diagnosis with MRI and 0 weeks for a diagnosis with IDA. Results: Direct costs to determine a knee diagnosis with IDA were $556 less expensive (California) to $470 more expensive (Massachusetts) than MRI. Assuming a 4-week wait, societal costs (indirect and direct) for knee diagnosis were anywhere from $7, 852 (Denver) to $11, 227 (Boston) less using IDA. Direct costs were similar for shoulder pathology. In order for MRI to be the less costly option, the MRI and the follow-up visit to the physician would need to occur directly after consultation. Under Medicare, direct costs were similar for both the knee and shoulder when comparing IDA and MRI. Including indirect costs resulted in IDA being the less costly option. Conclusions: The use of IDA instead of MRI for the diagnosis of knee and shoulder pathology reduced costs. The potential savings to society were approximately $7, 852 to $11, 227 per operative patient and were dependent on scheduling and follow-up using MRI and on Workers' Compensation. Level of Evidence: Economic and Decision Analysis Level IV . See Instructions for Authors for a complete description of levels of evidence.